Career Development Considerations for Academic Physician Mentees and Mentors in the Time of COVID-19: Jump in or Just Dip a Toe?. (July 2021) - Gettel, Cameron J.; Venkatesh, Arjun K.
Abstract : The COVID-19 pandemic has disrupted medical research, pushing mentors and mentees to decide if COVID-19 research would be germane to the early career investigator's developing research portfolio. With COVID-19 halting hundreds of federal trials involving non–COVID-19 research, mentors and mentees must also consider the broader moral calling of contributing to COVID-19 research. At the time of writing, the National Institutes of Health had responded to the pandemic with significant funding for COVID-19 research. However, because this pandemic is a new phenomenon, few mentors have expertise in the disease and relevant established resources. As a result, many mentors are unable to provide insight on COVID-19 research to early career investigators considering a pivot toward research related to this disease. The authors suggest 4 ways for mentees and mentors to respond to the changes the pandemic has brought to research funding and opportunities: (1) include COVID-19 research in existing portfolios to diversify intellectual opportunities and reduce funding risks; (2) negotiate the mentor–mentee relationship and roles and expectations early in project discussions—considering, as relevant, the disproportionate burden of home responsibilities often borne by early career faculty members who are women and/or from a minority group; (3) address any mentor limitations in content expertise; and (4) if the decision is to pivot to COVID-19 research, select projects with implications generalizable beyond this pandemic to other infectious outbreaks or to the redesign of health care delivery. Mentors and mentees must weigh the relevance of COVID-19 research projects to the postpandemic world and the amount of available funding against the developing interests of early career investigators. Academic medical centers nationwide must enable seasoned and early career researchers to contribute meaningfully to COVID-19 and non–COVID-19 research.